On analogical arguments: Organizing logical and conceptual problems in sections 18 and 19 of Schopenhauer´s The World as Will and Representation - Silva, Marcos (2011)
Here I list and organize some logical and conceptual problems in Section 18 (about the cognoscibility of the thing in itself) and Section 19 (about the extension of this result to the world) in Schopenhauer´s main work. When Schopenhauer put out the analogical argument for the responsibility for transmitting (übertragen) the problematic identification thing in itself/will, he brought to his philosophy the following fragile points of such an argument: (i) the logical invalidity; (ii) the lack of criterion for the extension scope; (iii) the indeterminacy of what is really being extended; (iv) the unrestricted character of his analogical extension; (v) the indirect nature of his argument (for avoiding the solipsism); and (vi) the collapse of what is being extended. I then try to point out why - despite these logical fragile points - the analogical argument seems not to be problematic at all to Schopenhauer.